PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN KOMPETENSI PROFESIONAL TERHADAP MUTU PEMBELAJARAN GURU - Enis Sumiati; Yayat Ruhiat; Suherman Suherman (Jurnal Education and Development, 2022)
Supervision of the principal's academy and professional competence are important things that need to be improved for the quality of teacher learning in Cluster 2, Serang District. Therefore, this article discusses the influence of Principal Academy Supervision and professional competence on the quality of teacher learning. In achieving the research objectives used descriptive analysis. The study was conducted on public elementary school teachers in cluster 2 Serang District with a sample of 41 teachers from 63 populations. In addition, to analyze the effect between variables, quantitative methods and descriptive multiple linear regression approaches were used. The results of the study (1) There is a significant effect between the academic supervision of the principal on the quality of learning based on the results of the t test of 3,247 > 2,023. (2) There is an effect of professional competence on the quality of learning from the results of the t-test 3,159 > 2,023. Simultaneously there is the influence of academic supervision and professional competence on the quality of learning with an R Square value of 0.583. This shows that the simultaneous effect is 58.3%. Based on this research, it can be said that academic supervision and professional competence have a positive and significant effect on the quality of learning for SDN teachers in cluster 2, Serang District.